The influence of organizational culture, organizational commitment, and work motivation on the performance of employees at the communication, informatics, cryptography and statistics service of erang regency - Ali Jaya; Ida Ida; Suparta Wijaya; Romli Ardie; Dian Wirtadipura (Institute of Accounting Research and Novation (IARN), 2025)
This study looks at how organizational culture, organizational commitment, and work motivation affect employee performance at the Communication, Informatics, Cryptography, and Statistics Office in Serang Regency. The research used a quantitative method with a survey to gather real data from employees. There were 69 participants, which covered all the employees in the office. Information was collected through questionnaires that measured how employees felt about organizational culture, their commitment to the organization, their motivation at work, and their performance. These questionnaires used a Likert scale to rate responses. The data was analyzed using multiple linear regression to see how much each factor influenced employee performance individually and together. Before testing the hypotheses, the data was checked for validity and reliability to make sure it was accurate and consistent. The results showed that organizational culture, organizational commitment, and work motivation all have a positive and significant impact on employee performance when considered together. This means that improving these three areas can help boost the quality and effectiveness of how employees perform. The R² value of 0.65 shows that 65% of the changes in employee performance can be explained by these three factors, while the other 35% is due to factors not covered in this study. These results show that building a strong organizational culture, increasing employee commitment, and improving motivation are important strategies for improving performance in public sector organizations.